PENGARUH PENGEMBANGAN SUMBER DAYA MANUSIA TERHADAP KINERJA PEGAWAI PADA PERUSAHAAN UMUM DAERAH (PERUMDA) AIR MINUM TIRTA TUAH BENUA KUTAI TIMUR - Arif Dharmawan (Tinta Nusantara 2018 Vol.1, 2026)
This Research aims to determine the effect of human resource development on employee performance at the regional public company (PERUMDA) Tirta Tuah Continental East Kutai drinking water. The sampling method using purposive sampling is a sampling technique with certain considerations in mind, namely by taking a number of samples with certain criteria to be used as a population sample in this research of 89 people. Research Results Based on the results of the F test for the hypothesis "it is suspected that there is a significant influence between human resource development on employee performance at the Regional Public Company (PERUMDA) Tirta Tuah Benua East Kutai Drinking Water" obtained a value of 42,151 and sign = 0.000. Because the significant value = 0.000 < 0.005, the hypothesis "it is suspected that there is a significant influence between human resource development on employee performance at the Regional Public Company (PERUMDA) Tirta Tuah Benua East Kutai Drinking Water" can be accepted.